Introduction to health care - Mitchell, Dakota; Haroun, Lee (Clifton Park, New York : Delmar Cengage Learning, 2012)
Offers an introduction to the foundational skills necessary for a range of health care professions, discussing basic clinical health care skills and emphasizing critical thinking skills needed in all health care professions.
Your career in health care -- Current health care systems and trends -- Ethical and legal responsibilities -- Medical terminology -- Medical math -- Organization of the human body -- Structure and function of the human body -- Growth and development -- Body mechanics -- Infection control -- Enrivronmental safety -- Lifestyle management -- Professionalism -- Lifelong learning -- The patient as an individual -- The communication process -- Written communication -- Computers and technology in health care -- Documentation and medical records -- Physical assessment -- Emergency procedures -- Controlling health care costs -- Performance improvement and customer service -- Job leads and the resume -- Interview, portfolio, and application -- Successful employment strategies.
Includes bibliographical references (pages 581-584) and index.
Keywords: MEDICAL CARE